2016
DOI: 10.1177/1090198115610572
|View full text |Cite
|
Sign up to set email alerts
|

Developing Theory to Guide Building Practitioners’ Capacity to Implement Evidence-Based Interventions

Abstract: Public health and other community-based practitioners have access to a growing number of evidence-based interventions (EBIs), and yet EBIs continue to be underused. One reason for this underuse is that practitioners often lack the capacity (knowledge, skills, and motivation) to select, adapt, and implement EBIs. Training, technical assistance, and other capacity-building strategies can be effective at increasing EBI adoption and implementation. However, little is known about how to design capacity-building str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 40 publications
2
117
0
Order By: Relevance
“…In perhaps the most exhaustive summary, Leeman and colleagues used an iterative process to review 24 capacity-building theories for their salient variations (i.e., how complexity and uncertainty influence the uptake of EBIs) (120). Several practice contexts are particularly important across the theories for capacity building.…”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
See 3 more Smart Citations
“…In perhaps the most exhaustive summary, Leeman and colleagues used an iterative process to review 24 capacity-building theories for their salient variations (i.e., how complexity and uncertainty influence the uptake of EBIs) (120). Several practice contexts are particularly important across the theories for capacity building.…”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
“…The gap between research and practice underscores the need to understand the barriers to uptake of EBIs (120). Several studies have reported practitioners’ personal and institutional barriers to utilizing EBIs.…”
Section: Why Capacity Building Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple centers have built on the workgroup’s curriculum to deliver and test local capacity-building interventions. 1214 Workgroup members collaborated a literature review to guide the design of capacity-building interventions 15,16 and collaborated on an NCI grant (4R01CA163526-05) to develop and test an online tool (IM Adapt) based on Intervention Mapping framework 17 that guides practitioners through a systematic process of selecting and adapting evidence-based interventions (EBIs) to fit their local community and context. 18 This project formed an advisory group with representatives from multiple CPCRN sites and is being beta tested.…”
Section: Resultsmentioning
confidence: 99%